Parseval-Goldstein type identities involving the L-4-transform and the P-4-transform and their applications - DERNEK, AYŞE NEŞE (TAYLOR & FRANCIS LTD, 2007)
In the present article the authors introduce several new integral transforms including the L-4-transform and the P-4-transform as generalizations of the classical Laplace transform and the classical Stieltjes transform, respectively. It is shown that the second iterate of the L-4-transform is essentially the P-4-transform. Using this relationship, a number of new Parseval-Goldstein type identities are obtained for these and many other well-known integral transforms. The identities proven in this article give rise to useful corollaries for evaluating infinite integrals of special functions. Some examples are also given as illustrations of the results presented here.
Keywords: L-2-transforms; Laplace transforms; Widder potential transforms; L-4-transforms; P(4-)transforms; Stieltjes transforms; K-transforms; Hankel transforms; Fourier sine transforms; Fourier cosine transforms; Parseval-Goldstein type theorems; L-2-TRANSFORM; TRANSFORM